Synchronous endometrioid adenocarcinomas in the uterine cervix and corpus. Issue 10 (29th June 2016) - Obata, Takeshi; Nakamura, Mitsuhiro; Mizumoto, Yasunari; Matsumoto, Takeo; Takakura, Masahiro; Fujiwara, Hiroshi
Abstract: It is frequently difficult to distinguish multiple primary carcinomas from single primary carcinoma with metastasis. Here, we report a case of synchronous endometrioid adenocarcinomas that independently occurred in the uterine cervix and corpus. A 47‐year‐old woman complaining of genital bleeding was preoperatively diagnosed with cervical adenocarcinoma with an endometrial lesion. On surgical treatment, two separate malignant lesions bearing endometrioid adenocarcinoma were identified in the uterine cervix and cavity. Although both lesions expressed the same type of human papillomavirus (HPV) gene, type 16, microscopic continuity was not observed. Furthermore, we detected a critical difference in PTEN mutation between the tumors and finally diagnosed this case as multiple primary cancers. This is the first report to show multiple primary endometrioid adenocarcinomas simultaneously arising in the uterine cervix and corpus. Considering the rarity of this case, the coexistence of HPV suggests its possible involvement in the carcinogenesis of the endometrioid adenocarcinomas.